CHARACTERISTICS OF THE EPIDEMICAL PROCESS OF ACUTE RESPIRATORY INFECTIONS IN THE REPUBLIC OF KARELIA IN THE MODERN PERIOD - L. V. Rubis (Журнал инфектологии)
Acute respiratory viral infections remain the most common group of diseases causing significant social and economic damage to society. Objective: to study the epidemiological characteristics of respiratory disease influenza and other etiology in the modern period in the Republic of Karelia – one of the most disadvantaged of this group of diseases regions of the country.Materials and methods: On the basis of statistical data and publications is analysed and compared with the performance of the country a long-term dynamics and of etiological structure of acute respiratory viral infections over the years 1980–2016, seasonality of morbidity in separate age and social groups of the population in the years 2013–2016, etiological structure allocated from sore viruses. On the basis of outpatient clinic investigated the clinical characteristics of acute respiratory viral infections in adult outpatients during the period of seasonal rise of morbidity.Results: it was found a marked reduction in the incidence of flu, partly due to clinical underdiagnosis of the infection, its rejuvenation, the prevalence of mild forms of influenza in adults; the increase in the incidence of infections influenza is not the etiology, mainly due to rhinovirus infection, forming a pronounced autumn rises, the lack of differences between the incidence of viral respiratory infections «organized» and «disorganized» children.Conclusions: in the modern period the epidemic process of acute respiratory viral infections has gained some new features, important from the point of view of the organization of preventive and curative interventions.